Application of The Cognitive-Technological Approach for Creating Online Courses on Digital Technologies for Teaching Staff - P. S. Lomasko; O. A. Fadeeva (Открытое образование (Москва))
Purpose of research. The revision and updating of approaches to the development of conditions and means for the implementation of advanced training programs for teachers in digital technologies in distance learning mode seems today to be an urgent and significant direction of scientific and pedagogical activity for the modernization of the system of additional postgraduate education in the Russian Federation. Training in such programs, as a rule, takes place on the basis of learning management systems in the format of online courses. The focus of this work is the problem of developing complex online courses, and not separate sets of digital didactic tools.The purpose of the study is to present the essence of the cognitive-technological approach and describe the most significant features of online courses on digital technologies for teaching staff developed on its basis.Materials and methods. The study has been conducted since 2018 based on the Regional State Autonomous Institution of Additional Professional Education “Krasnoyarsk Regional Institute of Advanced Training and Professional Retraining of Educators” and is devoted to solving the problem of improving the effectiveness of online training of teaching staff within the framework of advanced training programs in digital technologies.The working hypothesis of the study is the assumption that improving the effectiveness, satisfaction and providing conditions for the personification of teaching staff at advanced training courses in digital technologies can be provided if they are designed and developed on the basis of a cognitive-technological approach.Based on the analysis of scientific and pedagogical sources and the subsequent synthesis of cognitive and technological approaches existing in the didactic theory, the authors identified the key and most significant features that should be present in modern online courses on digital technologies for educators.Results. From a theoretical point of view, the paper describes the key characteristics of the cognitive-technological approach that define consolidated requirements for the description of goals, content, structure and conditions for the implementation of additional professional educational programs for advanced training created on its basis. From the perspective of practice, the paper presents possible ways to implement these requirements in online courses hosted in learning management systems (using the example of Moodle capabilities). An example of an online course on key digital competencies of teaching staff developed in this way is shown.Conclusion. The provisions described in the paper substantiate the need to find ways to improve the design technologies of advanced training and retraining programs focused on personification, high performance and conditions of the digital environment. The proposed characteristics, features and an example of the application of the cognitive-technological approach allow the implementation of such programs in the Moodle learning management system.The information presented in this paper may be of interest to teaching methods specialists designing additional professional educational programs for teaching staff; for developers and teachers of advanced training courses in digital technologies and their potential learners; for researchers in the field of digitalization of education.